Anticancer efficacy of the hypoxia‐activated prodrug evofosfamide (TH‐302) in osteolytic breast cancer murine models. (9th January 2016) - Liapis, Vasilios; Zinonos, Irene; Labrinidis, Agatha; Hay, Shelley; Ponomarev, Vladimir; Panagopoulos, Vasilios; Zysk, Aneta; DeNichilo, Mark; Ingman, Wendy; Atkins, Gerald J.; Findlay, David M.; Zannettino, Andrew C. W.; et al.
Abstract : This study assessed the cytotoxic activity of evofosfamide in vitro and evaluated its antitumor activity against osteolytic breast cancer either alone or in combination and paclitaxel in vivo. Evofosfamide cooperated with paclitaxel and exhibits potent tumor suppressive activity against breast cancer growth in the mammary gland and in bone. Abstract: Tumor hypoxia is a major cause of treatment failure for a variety of malignancies. However, hypoxia offers treatment opportunities, exemplified by the development of compounds that target hypoxic regions within tumors. Evofosfamide (TH‐302) is a prodrug created by the conjugation of 2‐nitroimidazole to bromo‐isophosphoramide mustard (Br‐IPM). When evofosfamide is delivered to hypoxic regions, the DNA cross‐linking effector, Br‐IPM, is released. This study assessed the cytotoxic activity of evofosfamide in vitro and its antitumor activity against osteolytic breast cancer either alone or in combination with paclitaxel in vivo. A panel of human breast cancer cell lines were treated with evofosfamide under hypoxia and assessed for cell viability. Osteolytic MDA‐MB‐231‐TXSA cells were transplanted into the mammary fat pad, or into tibiae of mice, allowed to establish and treated with evofosfamide, paclitaxel, or both. Tumor burden was monitored using bioluminescence, and cancer‐induced bone destruction was measured using micro‐CT. In vitro, evofosfamide was selectively cytotoxic under hypoxic conditions. In vivo evofosfamide was tumor suppressive as a single agent and cooperated with paclitaxel to reduce mammary tumor growth. Breast cancer cells transplanted into the tibiae of mice developed osteolytic lesions. In contrast, treatment with evofosfamide or paclitaxel resulted in a significant delay in tumor growth and an overall reduction in tumor burden in bone, whereas combined treatment resulted in a significantly greater reduction in tumor burden in the tibia of mice. Evofosfamide cooperates with paclitaxel and exhibits potent tumor suppressive activity against breast cancer growth in the mammary gland and in bone.